Vascular Malformation and Common Keratinocytic Nevus of the Soft Type: Phacomatosis Pigmentovascularis Revisited. (20th November 2014) - Laureano, André; Carvalho, Rodrigo; Amaro, Cristina; Freitas, Isabel; Cardoso, Jorge
Abstract : Phacomatosis pigmentovascularis is a rare syndrome characterized by the coexistence of a pigmented nevus and a cutaneous vascular malformation. We report a 5-year-old boy with all the typical findings of phacomatosis pigmentovascularis type Ia. Although its existence according to the traditional classification has been questioned, this case represents a very rare association of a capillary vascular malformation and a common keratinocytic nevus of the soft type.